Business Support for Emerging Entrepreneurs in Eco-tourism: North West, South Africa - Litheko, Alpheaus (Journal of Social Transformation and Regional Development, 2021)
This paper is based on the business support needed by emerging entrepreneurs to enter and participate in eco-tourism sector. Entrepreneurs play an important role in an economy as they can be key drivers of economic growth, innovation and job creation. Eco-tourism has been positively linked to job creation, entrepreneurship development and poverty alleviation. The aspect of ecotourism is closely linked with the idea of community empowerment. Against this background government is aiming to put policies, strategies and programs in place which aim to create an enabling environment for emerging entrepreneurs. Unfortunately, many emerging entrepreneurs’ business fail before reaching maturity, mainly due to inadequate business skills to establish and grow their enterprises, perpetuated by insignificant business support from government. South Africa has high levels of unemployment and severe problem of youth unemployment. This implies that the country needs to develop a policy framework that will comprehensively address issues of unemployment through a creation of economic opportunities. Entrepreneurship is one of the options that can reduce the unemployment rate and the social problems that are associated with unemployment. The objectives of this paper is to examine the business support needed by emerging entrepreneurs to facilitate their entry and participation in eco-tourism sector. Furthermore, to determine emerging entrepreneurs’ desire to participate in the sector in the North West province, South Africa. A combination of non-probability quota and convenience sampling were used, by surveying 160 respondents in the North West province, South Africa. The data extracted was analyzed using the Statistical Package for Social Science (SPSS). Results suggest that most respondents never received business support from government intervention programs, and had somewhat low levels of information concerning the economic opportunities associated with the eco-tourism sector.